Developing a framework for sacred grove management using stakeholder analysis: evidence from sacred groves in Gujarat, India. Issue 1 (29th April 2021) - Pandey, Amit; Sardana, Kavita; Gupta, Sandeep Kumar
Abstract : Purpose: The purpose of this study is to use the framework of stakeholder analysis in a participatory democracy, used in forest management planning, for arriving at the best management option for selected sacred groves of Kachchh. This is achieved by accounting for economic, cultural and ecological values and the resulting outcomes in the complex institutional mechanism. Additionally, this study provides a framework for complex decision-making that characterizes the management of sacred groves involving multiple criteria and options accounting for multiple stakeholders that involve conflicting interests. Design/methodology/approach: The analytical hierarchy process was used to calculate the global priorities of management options using the relative importance of stakeholders, weights of different decision criteria to arrive at the best management practice for selected groves of Kachchh. The global priorities of management options rank management practices based on stakeholders' values and their effects on the choice of management strategy as well as on the potential to attain a compromise between competing interests. For this purpose, survey responses of 141 individuals belonging to seven different stakeholder categories were analyzed. Along with focus group discussions, and personal interviews, a stratified random sampling technique was used to survey respondents. Findings: Based on the global priority weights of the alternatives, it is determined that the restoration management option (guggal is restored by planting new guggal sapplings, cattle grazing is prohibited and high levels of ecosystem goods and services are provided) had the highest score, followed by the preservation management option (grazing is allowed on the periphery, juvenile guggal is preserved and moderate ecosystem goods and services are provided). Therefore, restoration of sacred groves is the best management practice of sacred groves in West Kachchh, offering a compromise between maximizing provision of ecosystem services and economic benefits in terms of allowing cattle grazing. Originality/value: Though there are several studies on best management practices for community-owned forests, irrigation systems, and pasture lands, and the role of local institutions in sustaining these common-pool resources; such studies for sacred groves are absent, despite sacred groves being one of the longest surviving common-pool resources that has sustained it over several decades. This is the first study that uses the framework of stakeholder analysis to arrive at the best management practice for sacred groves. The uniqueness of the study lies in a comprehensive evaluation of ecological–economic–cultural interests of multiple stakeholders toward management of sacred groves.